Race tactic differences between elite east african an caucasian male 800m runners - Gyimes, Z. (New Studies in Athletics, 2013)
ABSTRACT Previous studies have shown genetic, cultural, and dietetic differences between athletes from East Africa and Caucasian athletes from Europe and North America that effect performance in endurance races. To date, no study has made a comparative analysis of race tactics in elite competition between the two groups. In contrast to the longer distance races where male East African athletes have clearly dominated international-level competitions in recent decades, there has been a relatively high number of successful Caucasian 800m runners, providing enough data to draw valid conclusions. The author studied major event finals and other international 800m races to try to identify statistically verifiable ethno-typical differences in tactics. He found that on average East African runners are keener to make fast starts and get closer to the lead in both championship and record-attempt situations while Caucasian athletes are more aggressive in the 400 to 600m segment of the race. Among the athletes studied, the mean average velocity in the final 200m of the race in both championship and record-attempt situations is approximately the same for both groups or slightly better for the Caucasian athletes.